Various Methods of Reconstruction of Axillary Burn Contracture (Bangladesh Journal of Plastic Surgery, 2014)
Post burn contracture is a burn sequel, which was not properly treated in initial burn management. Deep partial and full thickness burn of axillary region can result in scar contracture which limits shoulder abduction and extension. The axillary contracture has functional morbidity along with aesthetic disfigurement. Difficulties in rehabilitation of shoulder abduction during the initial period and the contractile evolution of the scar contribute to this problem. The goal of the surgical correction of axillary scar contractures is to provide a maximum release with minimum or no local anatomic distortion. 42 patients with post burn contracture of the axillas were operated in the Department of Burn and Plastic Surgery Unit, Dhaka Medical College Hospital and in National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka in the period between November 2007 & December 2011. Among them 26(61.9%) were males and 16(38.1%) were females. Age ranged from 6 to 38 years with a mean age 14.7 years. Unilateral axilla were involved in 34 patients(81%) and bilateral axilla was involved in 8 patients(19%). 18 cases (42.8%) had contracture of anterior axillary fold, 12 cases (28.5%) cases had contracture of posterior axillary fold, 8 cases (19%) had contracture of both folds and 4 cases (9.5%) had contracture involving axillary dome. Pre operative X-ray of shoulder joints of affected axilla revealed normal joint spaces. The operative procedure was chosen according to the pattern of scar and state of surrounding skin. Surgical procedures included release of post burn axillary contracture by recontructive procedures single Z plasties were done in 2 cases(4.7%), multiple Z plasties were done in 12 cases(28.6%), five flap plasty was done in 1 case (2.4%), local fascio cuteneous flaps were done in 25 cases(59.5%), parascapular flap was done in 1case (2.4%) and split thickness skin grafting was done in 1 case (2.4%). Axilla was immobilized with plaster cast for two weeks. The rate of complication was 9.5%. All of them were minor. Functional improvement was quite satisfactory, except for one case of skin grafting which had re-contracture. Choice of surgical procedure for reconstruction of post burn axillary contracture can be made according to the pattern of scar contracture and the state of surrounding skin. The choice of a flap should have priority to skin graft because of the superior functional and cosmetic results of flaps. Long term splinting and physical therapy are mandatory to prevent re contracture. Proper pre-operative planning, appropriate surgical method, post operative immobilization, physiotherapy and follow up can make good outcome of post burn axillary contracture reconstruction. DOI: http://dx.doi.org/10.3329/bdjps.v4i1.18686 Bangladesh Journal of Plastic Surgery January 2013, 4(1): 16-19